KAJIAN FENOMENOLOGI ASPEK MANIPULATING PADA KEMAMPUAN PSIKOMOTORIK PESERTA DIDIK DALAM PEMBELAJARAN PRAKTIKUM - Mahdinian Sri Sultanni; Suwahono Suwahono; Ella Izzatin Nada (Institut Pendidikan Tapanuli Selatan, 2023)
One of the evaluations in learning that must be carried out by every teacher is to assess the psychomotor abilities of students. The application of learning with the help of practical activities becomes a strategy in improving students' skills and assisting teachers in assessing their psychomotor abilities. This study aims to determine psychomotor abilities, especially in the aspect of manipulating students' reaction rates in learning at SMAN 8 Semarang. The basis of this research is the use of qualitative methods with a phenomenological approach. The sampling technique applied is purposive sampling technique with a sample of 14 students of class XI MIPA 5. Data were collected through a process of observation, interviews and documentation. The results of data analysis with the help of NVIVO software show psychomotor skills with different levels of ability in each indicator contained in the manipulation aspect. The location of the facilities in all sub-indicators of psychomotor abilities including the ability to measure volume and measure solution temperature